The Effect of Price, Brand Image, and Product Quality on the Purchase Decision of Aerostreet Products Among Generation Z TikTok Shop Users in Surakarta - Ananda Dito Pramudya Putra; Dwi Lestari, Wuryaningsih (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of price, brand image, and product quality on the purchase decision of Aerostreet products among Generation Z users of TikTok Shop in Surakarta. Employing a quantitative approach, data were collected through a structured questionnaire using a Likert scale, distributed online via Google Forms to 150 randomly selected followers of the @aerostreet account. The research focused on assessing consumer perceptions of price fairness, brand strength, and product quality, and how these variables affect purchase decisions measured by product appeal, repurchase intention, and confidence in choice. After eliminating incomplete responses, a total of 110 valid samples were analyzed using SPSS 23. Validity, reliability, and classical assumption tests were conducted to ensure data quality. The results show that all three independent variables—price, brand image, and product quality have a significant and positive impact on purchase decisions. Combined, these factors contribute to 6.7% of the variance in consumer decision-making. These findings highlight the importance of competitive pricing, strong brand identity, and high product standards in shaping consumer behavior, particularly in the context of social commerce platforms like TikTok Shop. The study also suggests expanding future research to other variables and broader regions for more comprehensive insights.